The Influence of Green Economy Policies on Company Marketing Strategies in Indonesia - Hadi, Seno Sudarmono (Dinasti Publisher, 2026)
This study examines the influence of green economic policies on the marketing strategies of companies in Indonesia. Using a qualitative approach, the study analyzes how different types of green economic policies influence the innovation strategies of manufacturing companies, identifies factors that facilitate or hinder the adoption of sustainable business practices, and evaluates the effectiveness of these policies in encouraging innovation. The results show that policies that combine regulation with economic incentives are most effective in stimulating sustainable innovation. Companies respond by increasing investment in clean technologies, adopting eco-design approaches, and even changing their business models. The effectiveness of these policies varies depending on company size, with SMEs facing greater challenges in adapting. The study also reveals the critical role of digital technologies in accelerating sustainable innovation, despite raising concerns about the digital divide. Key challenges identified include the risk of carbon leakage and the need for international policy coordination. The study concludes that while green economy policies have significant potential to drive the transformation of the manufacturing sector towards more sustainable practices, their implementation requires a cautious approach tailored to specific contexts. Recommendations include developing specific support programs for SMEs, enhancing international cooperation, and investing in education and infrastructure to support the transition to a green economy.